Pendampingan Dosen Pemula melalui Integrasi Artificial Intelligence dalam Program PKDP untuk Peningkatan Keterampilan Penulisan Ilmiah - Assaiq, Muhammad Royhan; Yumna, Hanin; Hayati, Siti Muna; Alwi, Mohammad Cholil; Saputro, Lilik Agus (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Scientific publications are an essential pillar in the development of novice lecturers' careers and institutional reputation, but are often hampered by technical obstacles and limited mastery of academic rules. To address this challenge, the 2025 Beginner Lecturer Competency Improvement Programme (PKDP) introduces innovation by integrating Artificial Intelligence (AI) into the Article Writing module. This study aims to analyse the implementation and impact of AI integration, focusing on two aspects: the strategy of its use to improve writing efficiency and the application of ethical principles to maintain academic integrity. It uses a qualitative approach through module content analysis, literature study, and semi-structured interviews with participants and facilitators. The study found that AI served as a co-author assistant in literature search, outlining, and language refinement. The application of the Dialogical Iterative Technique (DIT) was shown to reduce participants' cognitive load, allowing them to focus more on analysing and formulating original ideas. Despite increasing efficiency and confidence, the utilisation of AI also poses ethical challenges such as the risk of plagiarism, data fabrication, and over-reliance. This research recommends three ethical principles in the use of AI: challenge of use, validation of results, and commitment to originality. Thus, AI can be optimised as a productivity-enhancing tool without compromising scientific integrity